PERAN KYAI AGENG MOHAMMAD MESIR DALAM PENYEBARAN ISLAM DI DESA PODOREJO KECAMATAN SUMBERGEMPOL KABUPATEN TULUNGAGUNG 1790-1818 M - Sulis Rifamatul Muslimah; Rizal Zamzami (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2024)
This research discusses the role of Egyptian Kyai Ageng Mohammad in the spread of Islam in Ngadirogo Hamlet, Podorejo Village, Sumbergempol District, Tulungagung Regency, 1790-1818. Kyai Ageng Mohammad Egypt is a cleric who spread Islamic teachings and values ​​in Ngadirogo who previously embraced Hindu-Buddhist religion so he was able to convert the majority of Ngadirogo people to Islam. The aim of this research is to explain the biography and contribution of Kyai Ageng Mohammad Egypt in spreading Islam in Ngadirogo. The research method used is a historical research method with four stages, namely heuristics, verification, interpretation and historiography by utilizing oral data sources through interviews and library sources. The results of this research are that Kyai Ageng Mohammad Egypt contributed to spreading Islam in Ngadirogo by teaching the basics of Islam about monotheism and the pillars of Islam and establishing a mosque as a center for preaching. The preaching carried out by Kyai Ageng Mohammad Egypt spread beyond Ngadirogo, thereby creating a spiritual connection. with a student, namely Regent Raden Tumenggung Partowijoyo, who later influenced the change in the status of the Ngrowo Duchy to Tulungagung Regency.